BOTANICAL DESCRIPTION, MORPHOLOGICAL STRUCTURE ASSESSMENT OF SPINAEIA OLERACCA - Tatyana Vasilievna Kalashnova; Irina Alexandrovna Belyaeva (Современная наука и инновации, 2022)
Spinach is garden (Spinaeia оleracca L.) belong to the group of green vegetables with high maintenance of bioflavonoids, vitamins, mineral substances. Botanical and morphological descriptions of spinach garden (Spinaeia оleracca L.) are studied